Calculation of Nonlinear Stiffness of Rubber Pad under Different Temperatures and Prepressures - Chuanbo Xu; Mao-Ru Chi; Liangcheng Dai; Zhaotuan Guo (Shock and Vibration)
The static stiffness of rubber springs is affected by temperature and prepressure. In this thesis, the relationship between Young’s modulus and temperature of rubber was studied, and the quantitative relationship between them was determined. The approximate formula for calculating the static stiffness of rubber pads was further modified, and the ellipse approximation method and convexity coefficient correction method were proposed. In addition, the influence of temperature on geometric nonlinearity was considered. The formula for calculating nonlinear stiffness includes two variables: temperature and prepressure. The results of tests and theoretical calculations demonstrate that the nonlinear formula can be a good approximation and that it can meet the requirements of engineering applications.